SHORT COMMUNICATION: PRECAUSION ON THE USE OF BETA AGONISTS 2 IN PIG FARMS TO ENSURE THE QUALITY OF ANIMAL ORIGINATED-PRODUCTS - Tenaya, I Wayan Masa (Buletin Veteriner Udayana, 2023)
Based on the Veterinary Public Health Sciences aspects, animal originated-products for human consumption must have good quality. There are irregularities in the physical performance of pigs raised in certain breeders in Bali, such as the growth of meat muscles being very marked and unsuitable when viewed from the influence of genetic quality, feed, and maintenance management in general. From this discrepancy, there was an allegation of the use of Beta agonist 2 which had been banned by the government, which might still be given to pigs. The existence of business competition to reap high profits regardless of consumer health is an act against the law. Therefore, in this paper, the authors invite animal and community health observers within the One Health unit to supervise and take necessary actions.